Cvd-Deposited Oxygen-Selective Fluorinated Siloxane Copolymers as Gas Diffusion Layers - Cihanoğlu, Gizem; Ebil, Özgenç; Cihanoğlu, Gizem; Ebil, Özgenç (American Chemical Society, 2022)
Copolymer thin films of 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane (V4D4), 2-(perfluorohexylethylacrylate) (PFHEA), and 2-(perfluoroalkylethylmethacrylate) (PFEMA) were synthesized via initiated chemical vapor deposition (iCVD) as potential candidates for gas diffusion layers (GDLs) in gas diffusion electrodes (GDEs) for aqueous metal–air batteries. Thin-film GDLs exhibited an average water vapor transmission rate of 7.5 g m–2 day–1 and enhanced oxygen diffusion with oxygen permeabilities as high as 3.53 × 10–15 mol m m–2 s–1 Pa–1 (10.5 Barrer). The electrochemical performance of GDEs fabricated using commercial catalysts, current collectors, and synthesized GDLs was investigated by cyclic voltammetry, electrochemical impedance spectroscopy, and potentiodynamic polarization measurements. The fabricated GDEs exhibited higher oxygen reduction current densities (228.2 mA cm–2) compared to commercial GDEs (132.7 mA cm–2). Copolymer GLDs exhibited an order of magnitude higher oxygen diffusion (39.5 × 10–8 cm2 s–1) in GDEs compared to commercial counterparts (1.84 × 10–8 cm2 s–1). Due to the high oxygen solubility of V4D4 and excellent hydrophobic behavior of PFHEA and PFEMA, their copolymers can effectively promote the diffusion of oxygen and restrict moisture intake, making them ideal materials for GDLs. Combining well-balanced properties of siloxane and fluorinated polymer chemistries, the iCVD process is an excellent low-cost method for the fabrication of GDLs for metal–air battery applications.
Keywords: Diffusion; Copolymers; Oxygen; Batteries; Permeability